Adherence to the 2018 AHA cholesterol management guideline in hyperlipidemia treatment among adults in an outpatient setting - Behdani, Bahere; Kazemi, Toba; Zardast, Mahmood; Khosravi Bizhaem, Saeede; Jafari, Shima (Frontiers in Cardiovascular Medicine, 2024)
Background: Although there are evidence-based guidelines and effective treatments for dyslipidemia, there remains a significant disparity between guidelines and clinical practice. We investigated adherence to statin therapy per the 2018 ACC/AHA guideline recommendations.Methods: This is a retrospective, descriptive-analytical study of 1224 individuals who presented to the laboratories located in Birjand, eastern Iran, from June 2022 to March 2023. Analyses were conducted on 700 of these patients. Data collection tools involved a checklist and serum value measurements of laboratory factors deemed necessary for the study.Treatment was administered per the guidelines for 348 out of 700 individuals (49.7%).With 60.7%, the diabetes group exhibited the highest level of adherence to guidelines. In the ASCVD group, 31.7% followed the recommendations. The lowest adherence rates were in groups with 10-year ASCVD risk ≥ 20% and severe hypercholesterolemia, respectively (0% and 2.8%).In our study, atorvastatin was the most frequently prescribed statin, and the majority of patients consumed moderate-intensity statin. None of the patients who were classified as severely hypercholesterolemic achieved the LDL goal. Moreover, LDL-C goal achievement was low among the ASCVD population and patients with ASCVD risk ≥ 20% group.Hypercholesterolemia patients adhere inadequately to the AHA guidelines.Consequently, training courses are needed to inform medical doctors, particularly general practitioners, of the latest dyslipidemia treatment recommendations as the AHA advises.